2015
DOI: 10.4315/0362-028x.jfp-14-544
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Ohmic and Conventional Heating for Inactivation of Escherichia coli O157:H7, Salmonella enterica Serovar Typhimurium, and Listeria monocytogenes in Skim Milk and Cream

Abstract: Ohmic heating has proven advantages over conventional thermal processing and novel thermal alternative technologies. In this study, the effect of ohmic and conventional heating for pasteurizing skim milk and cream was examined. All treatment conditions for ohmic and conventional heating were identical except for composition of the heating chamber. In most cases, the reduction of three pathogens did not differ significantly between ohmic heating and conventional heating at fixed treatment temperatures and times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Similar results were also reported by other researchers. Kim & Kang () found that milk with 0%, 3%, and 7% fat content had no significant effect on the reduction of E. coli O157: H7 and Listeria monocytogenes during OH, however, the reduction of both pathogens decreased when fat content reached 10%. In contrast to OH, the reduction of both pathogens subjected to conventional heating was not affected by fat content.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar results were also reported by other researchers. Kim & Kang () found that milk with 0%, 3%, and 7% fat content had no significant effect on the reduction of E. coli O157: H7 and Listeria monocytogenes during OH, however, the reduction of both pathogens decreased when fat content reached 10%. In contrast to OH, the reduction of both pathogens subjected to conventional heating was not affected by fat content.…”
Section: Discussionmentioning
confidence: 94%
“…Fat is one of the most important components in meat and meat products, which contributes to the flavor, texture, mouth feel, juiciness, and overall sensation of lubricity (Muguerza, ). Previous studies indicated that heating time, EC, and inactivation effect of pathogens were significantly affected by fat content in milk during OH (Kim, Jo, & Kang, ; Kim & Kang, ). For meat and meat products, previous studies also indicated that fat content affected the EC of meat during thawing (Cevik & Icier, ; Liu et al, ) and heating (Bozkurt & Icier, ; Shirsat et al, ; Zell, Lyng, Cronin, & Morgan, ).…”
Section: Introductionmentioning
confidence: 96%
“…Milk has much higher water content which means it has higher heat transfer characteristics and higher a w, and can be more influential during heat treatment, especially in terms of thermal energy dissipation and shortage of come‐up time. In contrast, the higher fat content in margarine results in lower heat transfer rate and the need for a longer come‐up time (Kim & Kang, ). Another source of comparison could be meat products with high fat content since the thermal destruction of pathogenic bacteria is so important for them as well.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the higher fat content in margarine results in lower heat transfer rate and the need for a longer come-up time (Kim & Kang, 2015). Another source of comparison could be meat products with high fat content since the thermal destruction of pathogenic bacteria is so important for them as well.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Among alternative methods of pasteurization, ohmic heating (OH) stands out because it promotes rapid and uniform heating, resulting in less thermal damage to heat-sensitive compounds (Kim & Kang, 2015b;Lee, Sagong, Ryu, & Kang, 2012;Mesías et al, 2016;Moro & Arslanoglu, 2012). This technology consists of passing an alternating electric current (a moderate electric field, MEF) through a food with the main purpose of warming it by internal power generation.…”
mentioning
confidence: 99%